UNVEILING THE NEXUS BETWEEN E-HRM AND EFFECTIVENESS: HOW CULTURE SHAPES THE OUTCOMES - Zaheer Abbas; Shahid Mehmood; Sunila Pervez; Syed Usman Shah (Policy Research Journal, 2025)
Electronic Human Resource Management (E-HRM) systems are becoming increasingly important in improving organizational performance because of the quick digital transformation of organizational processes. This study looks at how E-HRM affects organizational effectiveness in Pakistan's IT-based sector, with an emphasis on the mediating function of organizational culture. A structured survey instrument was used to gather data from 200 IT company employees as part of a quantitative cross-sectional study design. The results show that by improving employee engagement and expediting HR procedures, E-HRM has a beneficial impact on organizational effectiveness. Additionally, company culture is a key mediating factor that increases the efficiency of E- HRM in accomplishing strategic objectives. The findings demonstrate that companies with flexible and cooperative cultures gain more from the use of E-HRM. This study contributes to the literature by integrating E-HRM, organizational culture, and organizational effectiveness into a cohesive framework, offering actionable insights for managers to align E-HRM initiatives with cultural values. The research underscores the critical interplay between technology and culture in driving organizational success, particularly in the dynamic IT sector of developing economies.